Analysing the detection and correction parameters in the homogenisation of climate data series using gsimcli - Ribeiro, Sara (2022)
Ribeiro, S., Caineta, J., Costa, A. C., & Henriques, R. (2015). Analysing the detection and correction parameters in the homogenisation of climate data series using gsimcli. In M. Painho, & F. Bação (Eds.), 18th AGILE International Conference on Geographic Information Science